The Relationship Between Family Role and Self-Care Patients with Schizophrenia - Devi Permatasari; Cucu Rokayah; Ruhyat Ejeb (GLOBAL HEALTH SCIENCE GROUP, 2019)
Schizophrenia is a serious disease that results in psychotic behavior, disruption in processing information, and interpersonal relationships, the prevalence of schizophrenia in Indonesia, which is around 400,000 people, patients with schizophrenia tend to experience a decrease in self-care. This is due to the decline in some brain functions that are owned by these patients which make it difficult to express emotions, withdraw from the social environment, lose motivation, not interested in doing daily activities, and ignore personal hygiene, to self-care schizophrenic patients need a family role. This study aims to determine whether there is a relationship between the role of the family and self-care in schizophrenic patients in the Outpatient Installation of the Mental Hospital of West Java Province. This study uses a quantitative method with a type of descriptive correlation research, using accidental sampling technique and cross sectional approach. The sample in this study amounted to 296 patient families. This study used a family role questionnaire and self-care questionnaire. The independent variables studied were the role of the family and the dependent variable studied, namely self-care. Univariate analysis uses frequency distribution and bivariate using chi-square. The results showed that patients had a good family role of 151 respondents (51.0%), and for self-care patients who needed as many as 125 (42.2%) assistive devices. There is a significant relationship between the relationship of the role of the family and self-care in schizophrenic patients p-value = 0.006. Keywords: self-care, family role